Bone regeneration after marginal bone resection in two-stage treatment of chronic long bone infection - a combined histopathological and clinical pilot study. Issue 10 (October 2022) - Wang, Gongteng; Alagboso, Francisca I.; Walter, Nike; Baertl, Susanne; Brochhausen, Christoph; Docheva, Denitsa; Rupp, Markus; Alt, Volker
Highlights: Marginal bone resection combined with local and systemic antibiotic therapy is a feasible treatment option to avoid large bone defects. Bone from the marginal resection area seems to have good regenerative potential. Intraoperative fast-cutting section analysis of could be of interest to determine adequate resection margins in chronic bone infections in the future. Abstract: Introduction: In chronic bone infection, marginal bone resection avoids large and difficult to reconstruct bone defects. However, there is still a lack of knowledge on bone regeneration during chronic bone infection and bone healing capability after marginal bone resection. Therefore, the purpose of this study was to investigate the clinical and histopathological outcomes after marginal bone resection in chronic long bone infection. We hypothesized that there is a regenerative bone healing potential after marginal bone resection that results in an acceptable clinical outcome and improved pathohistological bone healing parameters during treatment. Materials and methods: Nine patients were treated for chronic bone infections in a two-stage manner with marginal bone resection of the infected area and the placement of an antibiotic-loaded polymethyl methacrylate (PMMA) spacer at stage one followed by bone reconstruction at stage two combined with systemic antibiotic therapy. Comparable bone samples were harvested at the border region between vital and necrotic bone area during stage one and the identical location during stage two. Control bone samples were harvested from five healthy patients without bone infection. Clinical outcome in terms of infection eradication and bone consolidation were assessed. The phenotypic changes of osteocyte and morphological changes of lacunar-canalicular network were investigated by histological and immunohistochemical staining between the two observation periods. Furthermore, expression levels of major bone formation and resorption markers were investigated by immunohistochemical and tartrate-resistant acid phosphatase (TRAP) staining. Results: The clinical results with a follow-up of 12.9 months showed that eight of nine patients (88.9%) achieved bone consolidation after a planned two-stage procedure of marginal resection of necrotic bone and consecutive reconstruction. In four of the nine patients (44.4%), additional marginal debridements after stage two had to be performed. After marginal resection at stage one, the improved bone formation ability at stage two was demonstrated by significantly lower percentage of empty lacunae, significantly more mature osteocytes and higher BMP-2 positive cell density, whereas decreased resorption was indicated by significantly lower osteoclast density and RANKL/OPG ratio. In patients requiring additional debridement compared to patients without additional debridements, a significantly higher percentage of empty lacunae was found at stage one. Conclusion: Marginal bone resection combined with local and systemic antibiotic therapy is a feasible treatment option to avoid large bone defects as bone from the marginal resection area seems to have good regenerative potential. Despite a high revision rate of 44.4%, this technique avoids large bone resection and revisions can be done by further marginal debridements.